Distance Education Satisfaction During COVID-19 : Engineering Students’ Opinion According to the Six Thinking Hats Technique - Elmabaredy, Ahmed; Gencel, Nurgun; Semerci, Nuriye (Journal of Interdisciplinary Studies in Education, 2023)
This study aimed to investigate the distance education satisfaction during COVID-19 Pandemic from engineering students’ opinion according to the six thinking hats technique. The study sample consists of 209 students from the faculties of engineering in Turkey. A qualitative analysis was performed using the Nvivo12 software upon taking opinions with a questionnaire administered in the online environment. Considering the prominent themes in the six hats, students feel incompetent for their future career; exams are not conducted fairly in distance education; yet students have had the opportunity to improve themselves during this period. Furthermore, while proposing suggestions on the improvement of distance education, students also drew negative conclusions regarding the distance education delivered during the pandemic. With this study, a multidimensional investigation of the distance education received by students from the faculty of engineering in a situation such as a pandemic has been carried out.